Anthropometric knowledge and measurement evaluation among female volunteer community health workers in Depok - Sufyan, Dian Luthfiana; Arini, Firlia Ayu; Ilmi, Ibnu Malkan Bakhrul; Marjan, Avliya Quratul; Fatmawati, Iin (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: At the community level, assessment for children nutritional status is measured by female volunteer community health workers (FVCHW) through integrated health post (Posyandu). Based  on  initial  observation,  volunteers  have  sufficient  knowledge  of  anthropometric measurement however, to put it into practice, common pitfalls remain found.Refreshment on basic knowledge and practical training on anthropometric assessment is needed.Objectives:  As  part  of  Kampung  Caraka  Project  that  attempts  to  empower  locals  to  be deliberately  aware  of  community  health  and  well-being,  this  particular  study  aims  to  evaluate knowledge of FVCHW as well as their accuracy and precision on anthropometric assessment.Methods: This study is a quasi-experimental study with pre-posttest with control group design. The sample was purposively selected and 54 overweight adolescents were divided into a control group and two intervention groups. Education using healthy snacks quartet was conducted for 21 days  from  September  to  October  2023  in  Makassar  City.  Data  analysis  was  performed  using Wilcoxon singed ranks test.Results:  Results  showed  women  with  good  precision  for  MUAC,  height,  head  circumferences and length measurement were 23.1%, 23.1%, 53.8% and 33.3%, respectively. In contrast, only 7.7% of women had good accuracy on MUAC measurement. There is a significant difference of knowledge score before and after the education given (p-value 0.02, CI 95%).Conclusions:  The  cadre  had  good  precision  yet  poor  accuracy,  implying  the  necessity  of standardized procedure and regular equipment calibration prior to anthropometric measurement. There is a difference in mean scores before and after the education given, yet still denoted as low capacity. Further comprehensive education is highly required.